The Red Queen As A Symbol Of Misogynistic Fear Of Female Power In "Alice In Wonderland" (2010) - Wulandari, Dini Rahma; Indarwaty, Henny (Alphabet, 2026)
This study examines how the film Alice in Wonderland (2010) represents powerful women through the character of the Red Queen. Using a qualitative approach and Multimodal Critical Discourse Analysis (MCDA), this study explores how character design, gestures, dialogue, and visuals produce meanings about women and power. Research data was obtained from several scenes that depict the dynamics of power, emotions, and relationships between the Red Queen and other characters. The findings show that the Red Queen, despite being portrayed as a firm and dominant leader, is constructed through a patriarchal lens that marks her as an excessive, emotionally unstable, and dangerous figure. This image is reinforced through visual elements such as her enlarged head, striking makeup, and harsh commands. In contrast, the White Queen is portrayed as a gentle and “ideal” figure, creating a sharp contrast between women who are considered ‘good’ and ‘bad.’ Overall, this study reveals that the representation of the Red Queen not only presents an antagonistic character but also reflects the tendency of popular media to represent women in positions of authority as “otherness” and threatening figures.